LOADING AND UNLOADING LABOR PERFORMANCE AS A MEDIATION OF VARIABLES OF WORK MOTIVATION, WORK COMPETENCE AND WORK BEHAVIOR THAT IMPACTS WELL-BEING LOADING AND UNLOADING LABOR - Aswanti Setyawati; Yosi Pahala; Primadi Candra Susanto (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2022)
The purpose of the study  was to  find the influence between  variables with  quantitative research methods with analytical tools to search for data using SEM PLS,  the results of   the  study stated The value of the R square Adjusted equation  X2    = 0.634*X1 + e from the table above 0.396 indicates that 39.6% of the variance X2 can be explained by the change in the variable X1, while  the other 60.4% is due to other factors outside the model. From the results of  each variable, it   has a positive effect  and  the remaining results will later be continued by  other researchers for  other  variables.